Erythropoietin-regulated oxidative stress negatively affects enucleation during terminal erythropoiesis - Zhao, Baobing (Exp Hematol, 2016)
Differentiating erythroblasts are exposed to an oxidative environment. The dynamics of oxidative status during terminal erythropoiesis and how it affects cell differentiation in response to erythropoietin are unclear. Here we show that erythropoietin induces reactive oxygen species (ROS) production in the early stages of terminal erythropoiesis. The levels of ROS correlate with CD71 surface expression and the uptake of iron and transferrin. ROS decreases in the late stage of terminal erythropoiesis when the cells are preparing for enucleation. Consistently, treatment of erythroblasts with a low dose (5 mM) of N-acetyl-cysteine (NAC), an ROS scavenger, promotes enucleation. However, high dose (20 mM) NAC leads to significant cell death. Our study reveals an important function of erythropoietin in regulating the dynamics of oxidative status and enucleation.